Effect of organic and inorganic fertilization on the production and quality of Brachiaria brizantha - Apollon, Wilgince; Jean-Baptiste, Yviane; J. Wagner, Birmania; Luna-Maldonado, Alejandro; Silos-Espino, Héctor (Revista Mexicana de Ciencias Agrícolas, 2022)
The yield and bromatological composition of two cultivars of Brachiaria brizantha (Sinaí and Xaraés), in two soil types and three types of fertilizer, were evaluated by a completely randomized design with factorial arrangement (2x2x3) with four repetitions. The variables studied were yields of green matter, dry matter, number of leaves, as well as plant height, crude protein, the contents of calcium, phosphorus and crude fiber. The fertilizer factor had a positive effect on the variable plant height. With the application of bovine manure, the highest average height of 96.06 cm was obtained. At 21 days, the highest green matter yield of 756.2 kg ha-1 was obtained with the mineral fertilizer. The dry matter content was significantly influenced by the triple interaction (p≤ 0.05), where Sinaí achieved the highest average value of 132.5 kg ha-1 at 21 days of regrowth. The highest average CP content was found in plants of both varieties that received chemical fertilization. The highest average Ca content was found in Sinaí (1.9%) and Xaraés (2.08%), which received organic fertilization. While the highest average content of P was found in Xaraés (0.42%) with the application of AMF. Finally, the Sinaí plant that received bovine manure in sterilized soil had a higher average CF content (27.27%). Organic and inorganic fertilization had a significant effect on grass yield and nutritional quality.
Keywords: Brachiaria brizantha; bromatological composition; yield